Thematic Progression in Jack Ma Speech "We Never Give Up" and as an Alternate Source for Teaching Speaking - Septiana, Avin Nuzula; Sumardiyani, Listyaning; Susanto, Dias Andris (Allure Journal, 2023)
This research mostly concentrated upon the thematic progression discovered on Jack Mas speech "We Never Give Up". The current study attempts to identify thematic progression patterns on the speech, to show the most common sort of theme progression pattern found in the speech, to explained the thematic progression observe in the speech. The research design is Qualitative descriptive research. The research objective was Jack Mas "We Never Give Up" speech. The data from the speech script formed the study's instruments. The discussions from the study may conclude three kinds of thematic progression. There is a constant pattern with 136 findings, the zig-zag pattern with 14 findings, and a multiple pattern with 4 findings. The dominant type that being used in Jack Mas speech is constant theme. The constant patterns can be implemented by using the prior clause's rheme as the theme in the subsequent sentence, whereas the pattern of constant theme is generally applying since it is relatively simple to employ by repeating themes from the previous clause, the split theme pattern may be involved by taking rheme for two themes, and the multiple theme patterns can be employed when developing the following clause using a theme as a topic. As an alternate source for teaching speaking, thematic progression helps the watcher to understand the message from the speech and the result from thematic progression will provide information to the watcher.